Knowledge politics and post-truth in climate denial: on the social construction of alternative facts. Issue 2 (3rd April 2019) - Fischer, Frank
ABSTRACT: This article examines the post-truth debate and questions the argument that post-modernism and social constructivism is responsible for post-truth and alternative facts, including in climate denial. The article argues that social constructivism is not the problem but rather an epistemological orientation that helps us better understand the rise of post-truth. Toward this end, the essay examines the way empirical findings are translated into political knowledge and the role of science in "truth regimes". From this perspective, there is no amount of fact-checking alone that will resolve the post-truth problem. The argument is illustrated with the case of climate denial.